The contribution of tumour-derived exosomes to the hallmarks of cancer*. (3rd March 2016) - Meehan, Katie; Vella, Laura J
Abstract: Exosomes are small, biologically active extracellular vesicles and over the last decade, both stromal and tumour-derived exosomes (TDE) have been implicated in cancer onset, progression and metastases. Cancer is a complex disease that is underpinned by several "cancer hallmarks", originally described by Hanahan and Weinberg in 2000 and then revised in 2011. The hallmarks of cancer comprise six biological capabilities, along with two emerging hallmarks and two enabling characteristics that facilitate tumour growth and metastatic dissemination. Ample evidence supports a clear role for TDE in four of the original biological hallmarks (sustaining proliferative signalling, resisting cell death, inducing angiogenesis and activating invasion and metastases). A less-defined role exists for TDE in evading growth suppressors, and currently, there is no evidence to suggest a role for TDE in enabling replicative immortality. TDE are intimately involved in the newly defined hallmarks of cancer and enabling characteristics, most evidently in immune inhibition and tumour-promoting inflammation, which ultimately enable escape from immune destruction and tumour progression. Herein, we discuss the role of TDE in the context of the hallmarks and enabling characteristics of cancer as defined by Hanahan and Weinberg.